2021
DOI: 10.21203/rs.3.rs-846378/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness and safety of regdanvimab in patients with mild-to-moderate COVID-19: A retrospective cohort study

Abstract: Regdanvimab has decreased the time to clinical recovery from coronavirus disease 2019 (COVID-19) and lowered the rate of oxygen therapy according to the results from Phase 2 randomized controlled trial. More information is needed about the effects and safety of regdanvimab. We analyzed the medical records of patients with high-risk mild or moderate COVID-19 being admitted to Busan Medical Center between December 1, 2020, and April 16, 2021. A propensity score (PS) matched analysis was conducted to compare pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Increased age, male gender, higher body mass index and concurrent pneumonia were associated with increased odds of reaching the primary endpoint. Results for the overall cohort ( n = 377 for regdanvimab and 520 for no regdanvimab) were generally similar to those for the PSM cohort [ 20 ].…”
Section: Scientific Summarymentioning
confidence: 71%
See 2 more Smart Citations
“…Increased age, male gender, higher body mass index and concurrent pneumonia were associated with increased odds of reaching the primary endpoint. Results for the overall cohort ( n = 377 for regdanvimab and 520 for no regdanvimab) were generally similar to those for the PSM cohort [ 20 ].…”
Section: Scientific Summarymentioning
confidence: 71%
“…In a single-centre, retrospective, propensity score-matched (PSM) cohort study of patients with high-risk mild or moderate COVID-19, regdanvimab treatment was associated with a significant ( p < 0.001) reduction in the proportion of patients reaching the composite of death or disease aggravation versus no regdanvimab treatment (5.0% vs 21.5%; n = 377 in each group; primary endpoint) [ 20 ]. The odds ratios (95% CI) were 0.194 (0.112–0.320) and 0.169 (0.095–0.287) in univariate and multivariable-adjusted analyses, respectively ( p < 0.001 for both).…”
Section: Scientific Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Out of a total of 138 studies after removing duplicates, 12 full-text studies were assessed for eligibility. Four studies were excluded due to irrelevant data, 22,27 combination therapy 28 or review article. 29 Finally, 8 studies 16,20,21,[30][31][32][33][34] including 2 RCTs 16,32 and 6 observational studies 20,21,30,31,33,34 with 4793 patients were considered in the meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…Our study showed that regdanvimab was associated not only with a decreased need for oxygen supplementation but also with reducing remdesivir and dexamethasone requirements by 90% and 85%, respectively. In another study, regdanvimab usage reduced death, oxygen supplementation, and the need for intensive care unit care by 83.1% (95% CI, 71.3–90.5) [ 11 ]. Although the proportion of patients with disease progression was slightly lower in the present study, the difference could be attributed to the heterogeneity in defining clinical outcomes and the younger age of patients receiving regdanvimab (46.9 vs. 61 years) in our study.…”
Section: Discussionmentioning
confidence: 99%